2020
DOI: 10.1089/acm.2019.0413
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol as an Acute Stress Biomarker in Young Hematopoietic Cell Transplant Patients/Caregivers: Active Music Engagement Protocol

Abstract: Objective: Primary aims of the proposed protocol are to determine the feasibility/acceptability of the active music engagement intervention protocol during hematopoietic stem cell transplantation (HSCT) and clinical feasibility/acceptability of the biological sample collection schedule. Design: The authors propose a single-case, alternating treatment design to compare levels of child and caregiver cortisol in blood and saliva collected on alternating days, when the dyad receives and does not receive AME sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
(69 reference statements)
0
9
0
2
Order By: Relevance
“…Physicians have found music therapy as a method to alleviate patients who had shown regression and weak sociability during housing isolation. 150 Two types of patients, adults in the general ward of the hospital and children with leukaemia in an isolated room, have experienced it as an enjoyable practice. 151 impairment.…”
Section: Drug Tre Atmentsmentioning
confidence: 99%
“…Physicians have found music therapy as a method to alleviate patients who had shown regression and weak sociability during housing isolation. 150 Two types of patients, adults in the general ward of the hospital and children with leukaemia in an isolated room, have experienced it as an enjoyable practice. 151 impairment.…”
Section: Drug Tre Atmentsmentioning
confidence: 99%
“…As specified in our previously published protocol, the current study comprised two sets of aims (Russ et al, 2020). The primary aims were to: determine feasibility/acceptability of the AME intervention protocol during HSCT; evaluate clinical feasibility/acceptability of collecting data in this context, including collection of biological samples according to a rigorous schedule required when using a single-case design; and assess caregivers' perspectives about the collection of these samples.…”
Section: Current Studymentioning
confidence: 99%
“…To overcome these challenges, we used a single-case design study, which allows for estimation of intervention effects in small samples that are drawn from low-incidence populations. Details of the study protocol were published by Russ et al (2020), with outcomes reported in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Es ist unstrittig, dass Kortisol als akuter Biomarker für Stress angesehen werden kann [ 40 ]. In einigen Studien über die Wirkung von Musik und Stress wurde Kortisol als „Stressparameter“ herangezogen.…”
Section: Kortisol Stress Und Musikunclassified